Association of QRS Duration with Echocardiographic Left Ventricular Dimensions (Bangladesh Heart Journal, 2024)
Background: QRS duration (QRSd) is used to diagnose left bundle branch block (LBBB) and is important for determining cardiac resynchronization therapy eligibility. Others have reported associations of left bundle branch block (LBBB) and interventricular conduction delay with left ventricular (LV) systolic and diastolic dysfunction in patients without clinical HF. Individualized QRSd thresholds may improve diagnosis and intervention strategies. The goal of this study was to assess the relations of QRS duration to echocardiographic left ventricular (LV) dimensions in individuals.Methods: This was a hospital-based cross-sectional analytical study. A total of 134 purposively selected respondents were included in the study from the patients attending the outpatient or inpatient department of cardiology, Dhaka Medical College Hospital, advised for an echocardiogram. They were divided into two groups depending on their QRS complex duration (Group I≤100 ms and Group II>100 ms). After taking informed written consent, a case record form was filled and Echo measurements were taken following standard procedure with confidentiality.Results: Among the respondents, the mean age was found 52.68 ± 14.24 years. The majority were male (68%), and around 1/3rd of the respondents were overweight or obese. Males were found to have less QRS duration than females (p0.05). The study found that the interventricular septum thickness and inferolateral wall thickness were higher among those having a QRS duration of more than 100 ms (Group II), but this difference was not significant (p > 0.05). On the other hand, left ventricular diastolic dimension, systolic dimension, and left ventricular mass were found to be increased significantly (p